Module categories over finite pointed tensor categories - César Galindo (2012)
We study exact module categories over the representation categories of finite-dimensional quasi-Hopf algebras. As a consequence, we classify exact module categories over some families of pointed tensor categories with cyclic group of invertible objets of order p, where p is a prime number. © 2011 Springer Basel AG.